Analyzing the influence of the mRNA levels and DNA copy number on Breast cancer-related protein expression - Hassan, Abdullah Othman; Hassan, Rawaz Rizgar; Abdulaqadir, Shang Ziyad; Rashid, Rzgar Farooq (International Journal of Humanities and Education Development (IJHED), 2021)
Each protein's expression in breast cancers was examined to see if it was regulated at a specific molecular level, and whether this regulation was reflected in different molecular subtypes. Microarray technologies were used to examine the DNA, mRNA, and protein lysates of 251 breast carcinoma samples. It was possible to obtain data from all three levels of the PI3K/Akt pathway for 52 proteins that have been linked to cancer. In cis Spearman rank correlations between the three molecular levels were determined for every protein across all samples and for each intrinsic gene expression subtype, resulting in 63 comparisons total due to numerous gene probes matching to single proteins. The variance of subtype-specific correlation and the variations between overall and average subtype-specific correlation were used to study subtype-specific interactions between the three molecular levels. An external data collection of 703 breast tumor specimens was used to confirm the findings. There were four categories of proteins based on rank correlation values between the three molecular levels, with the proteins being sorted into each category. There were eight proteins in Group A that had a significant association between DNA copy number and mRNA expression (Bonferroni adjusted p 0.05), as well as the other way around. There were 14 proteins in Group B with a strong connection between mRNA levels and protein levels. There was a strong link between copy number and mRNA expression in the 15 proteins in Group C. No relationships were found between the remaining 25 proteins (group D). Identifying favorable associations between copy number levels, mRNA and protein expression was possible only when cancers were categorized according to their intrinsic subtype. Particular attention was paid to protein pairings that indicated large variance in correlation values between subtypes or the overall dataset. The basal-like subtype had the highest protein expression of cleaved caspase 7 and the lowest levels of hsa-miR-29c, which coincided with CASP7 gene expression. Low expression of CASP7 cleavage and low association to CASP7 gene expression were found in the luminal A-like subtype. This miRNA was found to have an apparent target sequence in CASP7 mRNA. As such, the hsa-miR 29c miRNA may be acting as a suppressor of CASP7 translation inside the luminal-A subtype. CCNB1 copy number and gene expression were shown to be unrelated across the entire cohort. Cyclin B1 mRNA and protein expression were found to be favorably associated to copy number data in most gene intrinsic subtypes, showing that copy number can influence overall protein expression. Each subtype's patients with decreased overall survival were recognized by aberrations of cyclin B1 copy number, as well. Genes and their products could be grouped into four groups based on the association between the three molecular levels, and the expression was anticipated to be regulated at distinct levels. Subtype-specific regulation was discovered after further stratification of the data set.